ANALISIS PERBANDINGAN PENGUJIAN BORE PILE MENGGUNAKAN SLT (STATIC LOADING TEST) DENGAN PDA (PILE DRIVING ANALYZER) (STUDI KASUS: PROYEK TSINGHUA KAMPUS, SERANGAN DENPASAR) - PRAGANINGRUM, TJOKORDA ISTRI; WANGSA, ANAK AGUNG RATU RITAKA; PRADNYADARI, NI LUH MADE AYU MIRAYANI; PUTRA, I WAYAN ANDIKA PRAYOGA (Universitas Mahasaraswati K. Mataram, 2024)
The foundation has an important role to transfer the structural load above it to the lower soil layer. To prove the accuracy of the calculation of the design of the carrying capacity of foundation piles in the field, it is necessary to carry out a test. The Tsinghua Campus Project is a project located in the Serangan area using a bore pile foundation with a diameter of 80 cm where to determine the carrying capacity of the foundation pile used Static Loading Test (SLT) and Pile Driving Analyzer (PDA) test methods. The purpose of this study is to determine the choice from the results of the comparison of implementation methods with the time and cost required in the two test methods. The method used in this study is through observation that visits directly to the field to look for aspects that need to be discussed to compare the two testing methods. The results of the Static Loding Test require a fee of Rp. 257,990,000.00 for testing 1 point of foundation piles and a test duration of 7 days for 1 test point, while the Pile Driving Analyzer requires more complex and more advanced reality models so that the results can be used in motion analysis. Then it is necessary to get a better way to separate the resistance of the shaft and the foot. However, please be aware that those using PDA results should understand that it is important to include information about subsoil and soil characteristics, groundwater and pore pressure, and other geotechnical matters and bring this information equivalent in quality to dynamic records. In addition to requiring a cost of Rp. 23,104,000.00 and the duration of the Pile Driving Analyzer test is for 2 days for 2 test points. The ultimate carrying capacity value of the Pile Driving Analyzer analyzer is known to be closest to the results of the Static Loding Test test interpreted by the Chin method